ICT in the research of the Bachelor’s Degrees in Child Education in Colombia: A State of the Art from the Last Decade - Molina Manosalva, Marlon Marcos; Tobos Valderrama, María Esther (Emerging Trends in Education, 2021)
The objective of this study is to reveal the state of the research production in relation to Information and Communication Technologies (ICT), in the BachelorDegreesin Early Childhood Education in the Universities of the Central Region of Colombia in theperiod 2009 -2019. To achieve thiswe propose,in the first place, to show the conception of ICT in the degree projectsanalyzed, to later identify the issues around which said investigations have revolved. The study is developed from the qualitative paradigm inspired by contemporary hermeneutics, since it seeks to understand the meaning in degree projects, in its context and historical development, taking the Hermeneutical Circle as a methodological process, as it is an explanatory resource of a dialogic type. The information gathering instrumentswere: the Bibliographic Matrix, the Matrix by Issues-Problems,and the Summary Card or Analytical File.As a result, we found that the conception of ICT in the Degree Projectsanalyzed is instrumental. Likewise, there are four trends around which ICT research has revolved: 1) ICT as a teaching means in childhood, 2) ICT in childhood interactions; 3) ICT policies in early childhood education,and4)knowledge of ICT in early childhood education.Keywords: State of the Art; Information and Communication Technologies(ICT); Child Education.